Standpunkt :
Between 28(1989):no.1 and 31(1992):no.1 inserted in the four different branch editions of DAG Journal (ZK 42096, ZK 42097, ZK 42098 and ZK 42099), since 31(1992):no.2 inserted in DAG Journal (ZK 40041).